Albumin–Folate Conjugates for Drug‐targeting in Photodynamic Therapy. (7th July 2016) - Butzbach, Kathrin; Rasse‐Suriani, Federico A.O.; Gonzalez, M. Micaela; Cabrerizo, Franco M.; Epe, Bernd
Abstract: Photodynamic therapy (PDT) is based on the cytotoxicity of photosensitizers in the presence of light. Increased selectivity and effectivity of the treatment is expected if a specific uptake of the photosensitizers into the target cells, often tumor cells, can be achieved. An attractive transporter for that purpose is the folic acid receptor α (FR α ), which is overexpressed on the surface of many tumor cells and mediates an endocytotic uptake. Here, we describe the synthesis and photobiological characterization of polar β ‐carboline derivatives as photosensitizers covalently linked to folate‐tagged albumin as the carrier system. The particles were taken up by KB (human carcinoma) cells within <90 min and then co‐localized with a lysosomal marker. FR α antibodies prevented the uptake and also the corresponding conjugate without folate was not taken up. Accordingly, a folate‐albumin‐ β ‐carbolinium conjugate proved to be phototoxic, while the corresponding albumin– β ‐carbolinium conjugates without FA were nontoxic, both with and without irradiation. An excess of free folate as competitor for the FR α ‐mediated uptake completely inhibited the photocytotoxicity. Interestingly, the albumin conjugates are devoid of photodynamic activity under cell‐free conditions, as shown for DNA as a target. Thus, phototoxicity requires cellular uptake and lysosomal degradation of the conjugates. In conclusion, albumin–folate conjugates appear to be promising vehicles for a tumor cell targeted PDT. Abstract : Folate‐tagged albumin mediates the endocytotic uptake of covalently attached photosensitizer molecules (cHa) into target cells (tumor cells), which thereby become photosensitive. The cytotoxicity of the particles totally depends on (1) the presence of the folate receptors (FRα) on the target cells and (2) the subsequent irradiation with light.